Penerapan Sistem Pendukung Keputusan Metode ROC dan ARAS dalam Seleksi Tim Kreatif Industri - Sholeha, Puspa Ayu; Aldisa, Rima Tamara (Journal of Information System Research (JOSH), 2024)
The process of selecting creative team members in the creative industry poses complex challenges. While aspects of formal and technical qualifications can often be clearly measured, elements such as creativity, innovation, and cultural fit are subjective factors that are difficult to measure objectively. Conventional selection methods are often not able to fully incorporate these qualitative aspects, which sometimes results in less precise or less than ideal evaluations. The criteria used in the selection of creative industry teams are portfolio, experience, innovation, technical skills, and collaboration. This emphasizes the need for research and development of more sophisticated and scalable selection methods in the context of the creative industry. The use of a Decision Support System (DSS) is the main focus for handling the problem. applying the ROC (Rank Order Centroid) method, which is utilized to give weight values to the selection criteria, and ARAS (Additive Ratio Assessment), which is utilized to provide the results of creative team selection decisions in the creative industry. The results of the study show that Lolly gets the highest score, which is 1.00000, and is selected as the most suitable creative team for the creative industry.